Correction of pincer nail deformity with dermal flap: a new technique in pincer nail deformity surgery - Altun, Serdar; Gurger, Murat; Arpaci, Enver; Inozu, Emre (Turkish Assoc Orthopaedics Traumatology, 2016)
Pincer nail deformity is the extreme, transverse, proximal-to-distal overcurvature of the finger, caused by osteophyte of the distal phalanx, and causing clamp effect on soft tissues and nail ingrowth. We report a new technique consisting of removal of the osteophyte causing clamp effect. Depressed areas of both side of the nail bed (lateral nail fold) were corrected with dermal flaps prepared from the side. Depressed areas were filled by these flaps, creating a smooth surface for the nail bed, and adequate correction was obtained.
Keywords: Dermal flap; pincer nail